2014
DOI: 10.1007/s10560-014-0338-4
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Maternal and Peer Influences on Sexual Intention among Urban African American and Hispanic Females

Abstract: Peer and family influences are interconnected in complex ways. These influences shape adolescent decision-making regarding engagement in sexual behaviors. Evidence indicates the more proximal (and direct) a process is to an individual, the more likely it is to affect his/her development and behavior. Therefore, family factors (e.g., parenting practices) and peer influence (e.g., peer norms) tend to be more strongly associated with adolescent behavior than distal factors (e.g., media or the economy). Guided by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…For black and Hispanic adolescent girls, the mother–daughter relationship typically aligns with behavioral outcomes (Barman-Adhikari, Cederbaum, Sathoff, & Toro, 2014; Hutchinson & Montgomery, 2007; Schinke et al, 2011). Lack of mother–daughter closeness has been shown in the literature to predict drug usage among adolescent girls (Schinke, Di Noia, Schwinn, & Cole, 2006).…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…For black and Hispanic adolescent girls, the mother–daughter relationship typically aligns with behavioral outcomes (Barman-Adhikari, Cederbaum, Sathoff, & Toro, 2014; Hutchinson & Montgomery, 2007; Schinke et al, 2011). Lack of mother–daughter closeness has been shown in the literature to predict drug usage among adolescent girls (Schinke, Di Noia, Schwinn, & Cole, 2006).…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…For example, family functioning, including higher levels of family support and decreased conflict, have been shown to prevent and reduce sexual risk behaviors and STI in Black adolescents (Crosby, Wingood, DiClemente, & Rose, 2002; Murry, Simons, Simons, & Gibbons, 2013). Given that differences in parents’ child-rearing practices and gender role expectations may exist among Black families (Barman-Adhikari, Cederbaum, Sathoff, & Toro, 2014; Howard, Rose, & Barbarin, 2013), researchers have shown that the influence of family functioning on Black adolescent sexual risk behaviors varies as a function of gender (Kogan, Brody, Chen, Grange, Slater, & DiClemente, 2010; Steiner, Swartzendruber, Rose, & DiClemente, 2014). Higher levels of family functioning, including parent-adolescent communication, has been associated with a lower likelihood of unprotected sex for Black females but not males (Kogan et al, 2010).…”
Section: Antecedents Of Sexual Risk Behaviors and Hiv/stimentioning
confidence: 99%
“…The study on parentadolescent sexual communication actually is the further development of the variable of parental influence or parent involvement. Numerous studies use communication as the indicator of parent involvement, as in the study conducted by Barman-Adhikari et al (2014). They measured parental influence based on several indicators, including parental monitoring, parentchild relationship satisfaction, and parent-teen sexual risk communication.…”
Section: Discussionmentioning
confidence: 99%